Phase Relations Associated With Mathematical Sciences: A Case Study - Gopinath, M. A.; Lakshmanamoorthy, A. (Journal of Information and Knowledge, 1983)
An analysis of quantitative data on the incidence of phase relations associated with mathematical sciences is presented. It has been found that application and bias phase relations have high percentage of incidence. Physical sciences show a greater tendency for phase relations with mathematics. It is also observed that intra-subject phase relations with mathematics is fairly frequent.